“Aqui é o crime, não é o creme”: facções criminosas, ética do crime e política criminal no estado do Ceará - Saraiva, Lívia Girão (2025)
This research aims to deepen the understanding of power relations between the State, criminal factions, and social institutions, focusing on Ceará and its capital, Fortaleza. Criminal factions are examined as structured social phenomena that transcend mere delinquency, operating as power structures both inside and outside prisons, often with implicit or explicit state acquiescence. The study addresses the Brazilian prison system, where the first national factions (PCC and CV) emerged, highlighting its role as a central environment for the consolidation of criminal communities. Rituals, ceremonies, and hierarchical practices are emphasized as key elements in shaping factional governance, allowing a reinterpretation of the political concept through the lens of the “politics of crime.” The research questions the effectiveness of criminal and penitentiary policies, pointing to the gap between official discourse and everyday practices, and to the selective tolerance of the State towards factional dynamics. It criticizes the predominance of repressive approaches and the lack of deeper analyses. The work contributes to moving beyond reductionist perspectives, proposing strategies that incorporate the social dynamics sustaining these organizations. It concludes with the urgency of structural reforms in public policies related to the criminal justice and penitentiary systems, through an intersectional and critical approach that integrates repression with broader sociopolitical analysis